PENERAPAN STRATEGI PEMBELAJARAN INDEX CARD MATCH DALAM MENINGKATKAN HASIL BELAJAR SEJARAH KEBUDAYAAN ISLAM (SKI) SISWA DI MI. HIDAYATUL MUBTADIIN II KADUR PAMEKASAN - Kamilah (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
The background of this research is the low student achievement MI. Hidayatul Mubtadiin II in the Islamic Cultural History (SKI) subject, particularly on the topic of Prophet Muhammad SAW's migration to Medina. This study aims to improve student learning outcomes through the implementation of the Index Card Match learning model. The research method used is Classroom Action Research (CAR), which consists of two cycles. Each cycle includes planning, implementation, observation, and reflection stages. The results showed that in the pre-cycle phase, student learning outcomes were still low, with most students not meeting the Minimum Mastery Criteria (KKM). In Cycle 1, there was an improvement in student performance, with a significant increase in the number of students achieving mastery. In Cycle 2, student learning outcomes improved further, with nearly all students meeting the mastery standard. These findings indicate that the implementation of the Index Card Match learning model can enhance students' understanding of the material taught. Thus, this learning model is recommended as an alternative to improve the quality of SKI learning in Madrasah Ibtidaiyah.